The LATAM’s Laozi: The Reception and Interpretations of the Laozi in Latin America - Costantini, Filippo (2022)
The Laozi has a long and variegated exegetical history inside and outside of China. This history shows the flexibility of a text that is always able to transform and adapt to the specific cultural context and historical period in which it emerges. Due to the expansion of Orientalism among Latin American intellectuals at the beginning of the 20th century, the Laozi, among other texts, began to propagate, producing a series of translations and original interpretations of the text. These works are the products of several Latin American writers who engaged with the Laozi mainly through the mediation of European and North American interpretations. From these cross-cultural interactions emerged some original interpretations and translations that created different ways of reading the Laozi. In this paper, I outline the major characteristics of the Laozi’s translations and interpretations in Latin America’s sub-regions. I draw a tentative sketch of what could be defined as the Latin American Laozi’s experience, better called the LATAM’s Laozi.